2017
DOI: 10.3389/fpsyt.2017.00251
|View full text |Cite
|
Sign up to set email alerts
|

Item Response Patterns on the Patient Health Questionnaire-8 in a Nationally Representative Sample of US Adults

Abstract: Recent studies have shown that item responses on the Center for Epidemiologic Studies Depression Scale (CES-D) and Kessler Screening Scale for Psychological Distress (K6) exhibit the same characteristic item response patterns among the general population. However, the distributional patterns of responses on the Patient Health Questionnaire-8 (PHQ-8) among the general population have not been adequately studied. Thus, we conducted a pattern analysis of PHQ-8 item responses among US adults. Data (18,446 individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…As reported previously, the degree of parallelism of these 16 lines reflects how decreasing ratios of “occasionally” to “some of the time” and of “all of the time” to “occasionally” are similar among the 16 depressive item scores after logarithmic transformation [ 8 ]. Because log-normal scales represent these decreasing ratios after logarithmic transformation, small differences in the ratios between two consecutive options do not have a great effect on the parallelism of the 16 lines [ 10 ]. Unlike the lines between “some of the time” and “occasionally,” some of the lines (“insomnia,” “failure,” and “dislike”) between “occasionally” and “all of the time” were further from parallel ( Fig 4B ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As reported previously, the degree of parallelism of these 16 lines reflects how decreasing ratios of “occasionally” to “some of the time” and of “all of the time” to “occasionally” are similar among the 16 depressive item scores after logarithmic transformation [ 8 ]. Because log-normal scales represent these decreasing ratios after logarithmic transformation, small differences in the ratios between two consecutive options do not have a great effect on the parallelism of the 16 lines [ 10 ]. Unlike the lines between “some of the time” and “occasionally,” some of the lines (“insomnia,” “failure,” and “dislike”) between “occasionally” and “all of the time” were further from parallel ( Fig 4B ).…”
Section: Resultsmentioning
confidence: 99%
“…Of note, previous studies have demonstrated that the ratios between two consecutive response options were similar among all depressive symptom items, with the exception of response options at the lower end of the curve [ 8 , 10 , 12 ]. In addition, these similar ratios between two consecutive response options have been shown to result in the same characteristic pattern of item responses described above: response-curve lines cross at a single point between the option at the lower end and the adjacent option, with a parallel pattern across the remaining options on a log-normal scale.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, lines of item responses crossed at a single point between “not at all” and “several days” and showed a parallel pattern for the remaining response options on a logarithmic scale ( 20 ). This common characteristic pattern has been replicated for PHQ-8 data from the Behavioral Risk Factor Surveillance Survey in the USA ( 21 ), data for the Center for Epidemiologic Studies Depression Scale (CES-D) from the Irish Longitudinal Study on Ageing ( 22 ) and the Japanese Active Survey of Health and Welfare ( 19 ), and data for the six-item Kessler Psychological Distress Scale (K6) from the National Survey of Midlife Development in the USA ( 23 ).…”
Section: Introductionmentioning
confidence: 67%
“…In the general population, item responses in self-rated depression scales have recently been reported to exhibit a characteristic distribution ( 19 21 ). In an analysis of PHQ-9 data from the NHANES in the USA, we found that item responses for the PHQ-9 exhibited a common pattern across all nine items ( 20 ).…”
Section: Introductionmentioning
confidence: 99%